2011
DOI: 10.1111/j.1476-4431.2011.00694.x
|View full text |Cite
|
Sign up to set email alerts
|

Sleep aid toxicosis in dogs: 317 cases (2004–2010)

Abstract: Overall, the prognosis for dogs with sleep aid medication toxicosis was excellent, and no fatalities were reported in this clinical population. As significant clinical signs can still be seen with ingestion, appropriate decontamination is warranted in asymptomatic patients via emesis or gastric lavage, followed by activated charcoal administration. Symptomatic patients should be hospitalized for monitoring and supportive care for a minimum of 12 hours or until clinical signs resolve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 17 publications
(31 reference statements)
2
6
0
Order By: Relevance
“…Our epidemiological study showed high exposure to zolpidem (Richardson and others 2002, Lancaster and others 2011) and only one dog-related case involving zoplicone, an eszoplicone stereoisomer (Lancaster and others 2011). No cases were recorded involving cats, rarely reported in literature (Czopowicz and others 2010).…”
Section: Discussionmentioning
confidence: 73%
“…Our epidemiological study showed high exposure to zolpidem (Richardson and others 2002, Lancaster and others 2011) and only one dog-related case involving zoplicone, an eszoplicone stereoisomer (Lancaster and others 2011). No cases were recorded involving cats, rarely reported in literature (Czopowicz and others 2010).…”
Section: Discussionmentioning
confidence: 73%
“…Representative GABA-A receptor modulators and a histamine inverse agonist, which tend to promote sleep in most species but have paradoxical hyperarousal effects in dogs according to qualitative reports in the canine veterinary literature (Barnett et al, 1984; Bertini et al, 1995; Richardson et al, 2002; Wismer, 2002; Herron et al, 2008; Lancaster et al, 2011; Giorgi et al, 2012), were also evaluated in the sleep studies as potential control sleep-inducing substances for the salience arousal studies. Diazepam was purchased from Sigma-Aldrich, eszopiclone from Sunovion Pharmaceuticals, zolpidem from Teva Pharmaceuticals, and diphenhydramine from Henry Schein.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, since the veterinary literature qualitatively cites case studies of accidental GABA-A receptor modulator and antihistamine ingestion causing paradoxical hyperarousal in healthy dogs (Barnett et al, 1984; Bertini et al, 1995; Richardson et al, 2002; Wismer, 2002; Herron et al, 2008; Lancaster et al, 2011), we quantitatively pre-tested several representative drugs via polysomnography (PSG) to determine whether we could evaluate different pharmacological hypnotic mechanisms in the salience gating arousal paradigm.…”
Section: Introductionmentioning
confidence: 99%
“…In clinically affected dogs,~50% exhibited signs of CNS depression and~50% exhibited signs of CNS stimulation, while anorexia, vomiting and diarrhoea occurred in~20% of cases; no deaths occurred (Lancaster et al, 2011). Zolpidem was the most frequent non-BZD sleep aid medication involved in cases of dog poisoning reported to CAV (Caloni et al, 2014).…”
Section: Non-benzodiazepine Sedative-hypnotic Drugsmentioning
confidence: 97%
“…The Pet Poison Helpline recorded 240 cases of zolpidem ingestion in dogs from 2004 to 2010; 66% of dogs remained clinically unaffected (median dose 0.9 mg/kg) while 34% developed clinical signs (median dose 1.47 mg/kg) (Lancaster et al, 2011). In clinically affected dogs,~50% exhibited signs of CNS depression and~50% exhibited signs of CNS stimulation, while anorexia, vomiting and diarrhoea occurred in~20% of cases; no deaths occurred (Lancaster et al, 2011).…”
Section: Non-benzodiazepine Sedative-hypnotic Drugsmentioning
confidence: 97%